2019
DOI: 10.1016/j.pgeola.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrate trace fossils from the Alveley Member, Salop Formation (Pennsylvanian, Carboniferous), Shropshire, UK

Abstract: The late Carboniferous-early Permian was a period of major environmental change, with the rainforests that covered the equatorial zone during the Carboniferous disappearing due to increasing aridification. This environmental transition had significant impacts on the terrestrial biota, including a major extinction event among plant and vertebrate groups. A rich and unique ichnofauna from the Alveley Member (Moscovian: Westphalian D) of the Salop Formation at Alveley in Shropshire

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This agrees with the review from Mørk et al (2014), based on the original work in Worsley et al (2001), who suggested that the Kapp Hanna Formation is formed by floodplain and valley-fill deposits due to rivers draining to the northwest, as the island was tilted up in the east at this time. Similar facies have previously been interpreted as formed in a floodplain environment with a persistently high water table (Tucker & Smith, 2004;Hedge et al, 2018). of 17 Without better age constraint on the Kapp Hanna Formation, its context regarding the Carboniferous rainforest collapse remains uncertain given that well-drained, seasonally dry environments were common even in the pre-collapse Pennsylvanian wetlands of the so-called coal age (DiMichele et al, 2010).…”
Section: A Late Carboniferous River Valley -Palaeoenvironmental Contextmentioning
confidence: 80%
“…This agrees with the review from Mørk et al (2014), based on the original work in Worsley et al (2001), who suggested that the Kapp Hanna Formation is formed by floodplain and valley-fill deposits due to rivers draining to the northwest, as the island was tilted up in the east at this time. Similar facies have previously been interpreted as formed in a floodplain environment with a persistently high water table (Tucker & Smith, 2004;Hedge et al, 2018). of 17 Without better age constraint on the Kapp Hanna Formation, its context regarding the Carboniferous rainforest collapse remains uncertain given that well-drained, seasonally dry environments were common even in the pre-collapse Pennsylvanian wetlands of the so-called coal age (DiMichele et al, 2010).…”
Section: A Late Carboniferous River Valley -Palaeoenvironmental Contextmentioning
confidence: 80%
“…Protichnites gallowayi is most similar to trackways assigned to the ichnogenus Palmichnium , in its external width, wide medial impression, morphology and proportions of the tracks, and their arrangement as series. Palmichnium comprises Palmichnium palmatum , the type ichnospecies, made by a eurypterid using a subaerial flop-type maneuver, leaving coxal imprints; Palmichnium antarcticum (Gevers et al, 1971; Hedge et al, 2019), made by stylonurids; Palmichnium capensis (Anderson, 1975), made by an onychopterellan using a subaqueous hop-type maneuver (Braddy and Almond, 1999); Palmichnium stoermeri Briggs and Rolfe, 1983, made by a mixopterid, with a staggered symmetry; Palmichnium kosinskiorum , made by a hibbertopterid; Palmichnium macdonaldi Braddy, 1995, made by a swimming adelophthalmid; and Palmichnium pottsae Braddy and Anderson, 1996, made by a walking adelophthalmid with an irregular symmetry (Poschmann and Braddy, 2010). Palmichnium culmicum Pfeiffer, 1968 lacks tracks and therefore should be excluded.…”
Section: Systematic Paleontologymentioning
confidence: 99%